Improving creativy and learning motivation in basketball through tactical approach - Hartati Hartati; Meirizal Ursa; Bayu Hardiyono; Rendi Wira Jaya (LPMPP Universitas Negeri Yogyakarta, 2022)
Students assumed that learning basketball is less fun and students did not seem interested in following it. The purpose of this study was to determine the effect of a tactical approach in basketball learning on creativity and motivation. The method used in this study was